Physico-chemical characterization of macusanite and inclusions: A volcanic glass from peruvian andes - De Azevedo, Murilo Candido [UNESP]; Dos Santos, Luis Fernando [UNESP]; Pereira, Luiz Augusto Stuani [UNESP]; Sáenz, Carlos Alberto Tello [UNESP]; Teixeira, Silvio Rainho [UNESP]; Figueroa, Pedro (FapUNIFESP (SciELO), 2021)
Macusanite is a volcanic glass extracted from the volcanic field Macusani - Peru, formed by the fast cooling of magma. This study shows physical and chemical characterization of Macusanite samples to better understand its molecular structure, elemental composition as well as to investigate the presence of natural inclusions. The characterization of the natural glass can give valuable geological information about the magma composition, the eruption intensity and age of volcanism activity. Moreover, the use of different characterization techniques can help in mineral prospecting. Macusanite was characterized by X-Ray Diffraction/Fluorescence (XRD/XRF), Optical Microscopy, Scanning Electron Microscopy (SEM) and micro-Raman spectroscopy. The latter suggests the presence of andalusite mineral incorporated in the glass structure, while the Energy-Dispersive X-ray Spectroscopy (EDS) analysis indicates the presence of some rich calcium inclusion. Moreover, XRD shows the glass characteristic amorphous band and that the sample is in the glassy stage.
Keywords: Characterization; Macusanite; Mineral inclusion; Volcanic glass